Indonesia: Indonesia - syahroni fadhil, Ahmad (Jurnal Yuridis, 2023)
Indonesia is a country rich in natural resources, therefore the presence of law is important to achieve sustainability and protection of these natural resources. One of the natural resources regulated in legal regulations is water. Water is a natural resource that is important for life on earth or in other words, water is the essence of life on earth. Concerns about the availability of water for Indonesian people often led to conflict during the colonial period and the lex specialis regulations regarding guarantees of the right to clean water for the community had not yet been established.